ANALISIS PERSEPSI KONSUMEN DALAM MEMPENGARUHI MINAT PENGGUNAAN E-WALLET SEBAGAI ALAT TRANSAKSI (Studi Pada Mahasiswa Universitas Samawa Sumbawa Besar) - Sulistianingsih, S; Pamungkas, Binar Dwiyanto (Samalewa: Jurnal Riset & Kajian Manajemen, 2024)
This study aims to analyze consumer perceptions in influencing the interest in using e-wallets as a transaction tool for students of Samawa University, Sumbawa Besar, which in this study consists of perceptions of convenience and perceptions of risk. The type of this study was associative study. The type of data used in this study was quantitative data obtained directly from research respondents using a questionnaire. The respondents in this study numbered 85 students, who were determined using non-probability sampling techniques with the accidental sampling method. The data used in this study were processed with SPSS software for analysis using multiple linear regression analysis techniques, partial hypothesis testing (t test), simultaneous hypothesis testing (F test), and determinant coefficient testing (R2). The results of this study showed that in partially the perception of convenience had a positive and significant effect on the interest in using e-wallets, while the perception of risk had a negative and significant effect on the interest in using e-wallets as a transaction tool for students of Samawa University. In simultaneously, the perception of convenience and the perception of risk had a significant effect on the interest in using e-wallets as a transaction tool for students of Samawa University. The effect of perception of convenience and perception of risk on the interest in using e-wallets as a transaction tool for students at Samawa University was 58.4%, while the remaining of 41.6% was effected by other variables outside this research model, such as perceived usefulness, trust and user attitudes.